Gastric proliferative lesions induced by duodenogastric reflux in rats - Monteiro, Rosângela Lucinda Rocha; Andreollo, Nelson Adami; Rodrigues, Maria Aparecida Marchesan [UNESP]; Araujo, Marina Raquel (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2006)
OBJETIVO: Avaliar as lesões proliferativas que se desenvolvem na mucosa gástrica de ratos Wistar após modelo específico de refluxo duodeno-gástrico. MÉTODOS: Foram utilizados 75 ratos adultos machos divididos em três grupos experimentais: o grupo I (controle) submetido a gastrotomia na parede posterior do estômago glandular (25 animais); o grupo II (RDG), foi submetido a gastrojejunoanastomose látero-lateral na parede posterior do estômago glandular (25 animais) e o grupo III (RDG-P) submetido a gastrojejunoanastomose látero-lateral na parede posterior do estômago glandular, com secção e fechamento da alça (25 animais). Os animais foram observados durante 36 semanas, após o que foram realizados estudos macroscópicos e microscópicos da anastomose gastrojejunal, da região pré-pilórica e região escamosa do estômago. RESULTADOS: Os animais do Grupo I não apresentaram nenhum tipo de lesão. No grupo II observou-se 40% de lesões do tipo hiperplasia adenomatosa na anastomose e 12% de hiperplasia escamosa. No grupo III obteve-se 40% de hiperplasia adenomatosa na mucosa pré-pilórica, 72 % de hiperplasia adenomatosa na mucosa da anastomose, 20% de hiperplasia escamosa e 12 % de adenocarcinoma. CONCLUSÕES: O refluxo duodeno-gástrico induz a alta freqüência de lesões proliferativas na mucosa adjacente à anastomose gastrojejunal ou na mucosa pré-pilórica e o adenocarcinoma é um evento raro neste modelo experimental.

PURPOSE: To analyze mucosal proliferation and its characteristics, through specific models of duodenogastric reflux, in the stomach of Wistar rats. METHODS: Seventy-five healthy and adult male rats were divided into three groups: group I - control (n = 25 animals), submitted to gastrotomy of the posterior wall of the glandular stomach; group II - DGR (n = 25 animals), submitted to duodenogastric reflux through latero-lateral gastrojejunal anastomosis in the posterior wall of the glandular stomach and group III - DGR-P (n = 25 animals), submitted to duodenogastric reflux through the pylorus following the same procedure of group II, sectioning and closing the afferent loop. The animals were observed during 36 weeks and subsequently the mucosal lesions were analyzed, with macroscopic and microscopic examination of the prepyloric, the gastrojejunostomy and the squamous area of the stomach. RESULTS: Group I did not present any kind of lesion. Macroscopic lesions of the prepyloric area in groups II and III were 0% and 20%, respectively. Macroscopic lesions of the gastrojejunal stoma in groups II and III were 36% and 88%, respectively, and 12% and 28%, respectively, in the squamous area. Microscopically, adenomatous hyperplasia (AH), squamous hyperplasia (SH) and adenocarcinoma (AC) were diagnosed. The occurrence of AH at the prepyloric area in groups II and III was 0% and 40%, respectively, and in the gastrojejunal stoma, 40% and 72%, respectively. The occurrence of SH in the squamous area in groups II and III was 12% and 20%, respectively, without statistical differences between the groups. AC was found only in three animals of groups III (12%). CONCLUSIONS: The duodenogastric reflux in this experimental model caused high frequency of proliferative lesions of the gastrojejunal stoma and in the prepyloric area, while adenocarcinoma was a rare occurrence.
Lesões proliferativas gástricas induzidas pelo refluxo duodenogástrico em ratos
Keywords: Refluxo Duodenogástrico; Hiperplasia; Adenocarcinoma; Ratos; Duodenogastric Reflux; Hyperplasia; Adenocarcinoma; Rats